1991
DOI: 10.1002/ijc.2910490323
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human granulocyte colony‐stimulating factor inhibits the metastasis of hematogenous and non‐hematogenous tumors in mice

Abstract: We studied the effects of in vivo administrations of recombinant human granulocyte colony-stimulating factor (rhG-CSF) on the metastasis of murine hematogenous and non-hematogenous tumors in spontaneous and experimental metastasis models. Spontaneous lung metastasis caused by intra-footpad injections of B16-BL6 melanoma and Lewis-lung-carcinoma (3LL) cells were inhibited by intravenous (i.v.) and subcutaneous (s.c.) injections of rhG-CSF after excision of the primary tumors. Recombinant hG-CSF significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Interestingly, circulating granulocytes in many cancer patients have been reported to be impaired in their ability to produce superoxide anion (Hara et al, 1992), to perform antibody-dependent tumor cell lysis (Dallegri et al, 1989), and to mobilize in vivo to skin chambers (Frumento et al, 1984). While PMNs are normally a scarce reactive component of both human and animal tumors (Di Carlo et al, 2001), it has been suggested that these cells are active in immunosurveillance against several tumors (Di Carlo et al, 2001;Matsumoto et al, 1991;Midorikawa et al, 1990). During rIL-2 infusion in patients with malignant melanoma and renal cell carcinoma, there has been phenotypic and functional evidence of potent PMN activation (Di Carlo et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, circulating granulocytes in many cancer patients have been reported to be impaired in their ability to produce superoxide anion (Hara et al, 1992), to perform antibody-dependent tumor cell lysis (Dallegri et al, 1989), and to mobilize in vivo to skin chambers (Frumento et al, 1984). While PMNs are normally a scarce reactive component of both human and animal tumors (Di Carlo et al, 2001), it has been suggested that these cells are active in immunosurveillance against several tumors (Di Carlo et al, 2001;Matsumoto et al, 1991;Midorikawa et al, 1990). During rIL-2 infusion in patients with malignant melanoma and renal cell carcinoma, there has been phenotypic and functional evidence of potent PMN activation (Di Carlo et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, highly increased hIL-6 expression is a common feature of many tumor cells aside from those found in KS (5,38,72,78); thus, IL-6 and SOCS3 could act in a wider context in immunomodulation in tumor biology. Neutrophil exclusion from KS lesions is likely to have pathological implications, as several studies strongly support the concept that they are important in immunosurveillance against various tumor types (18,43,44). Neutrophils, which are recruited early to such sites, produce cytotoxic mediators, including proteases, reactive oxygen species, and soluble mediators of cell killing, and antiviral agents such as TNF-␣ and gamma interferon (IFN-␥) (34).…”
Section: Discussionmentioning
confidence: 99%
“…46 It has been reported that activated PMNs play a key role in immunosurveillance against several tumors, such as melanoma, lung carcinoma and adenocarcinoma. [47][48][49] In cooperation with CD8 þ cells, they are also involved in the cytokine-induced tumor rejections. 50 In this context, it is likely that the immune responses elicited by rAAV-hTERTC27 will be even more prominent in immunocompetent animals.…”
Section: Raav-htertc27 Treatment Induces Differential Expression Of Gmentioning
confidence: 99%